Analisis Kelayakan Finansial dan Nilai Tambah Agroindustri Skala Rumah Tangga Berbasis Ubikayu Di Kabupaten Barito Koala, Kalimatan Selatan - Elisabeth, Dian Adi Anggraeni; Prasetiaswati, Nila (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Financial feasibility and added value analysis of home scale-agroindustries development based on cassava commodity in Barito Koala District, South Kalimantan. Cassava processing into food products aimed to improve shelf-life of fresh cassava in order to be feasible to be consumed and to give added value in order to improve cassava’s selling value. Prospect of home scale-agroindustries development based on cassava was observed by analyze their financial feasibility and added value. Research location was detemined using purposive sampling method; while sample taking was determined using simple random sampling and key person methods. Data obtained was analyzed using both qualitative and quantitative descriptive methods. Stages of financial feasibility and added value analysis were production cost analyses, revenue, benefit, and efficiency (B/C ratio), and added value. Home scale-agroindustries based on cassav in Barito Koala District have prospect to be developed. However, with B/C ratio greater than 1 (1.67), cassava chips industry has more chance to be developed due to it is more efficient and feasible. The highest added value ratio as well as benefit ratio i.e. 63.13% and 90.79% respectively, showed that the chips indsutry can give the high added value and benefit for producer.